Choice Overload and the Senior Population; Guidelines for a Designer. - Flamm, Sara L. (My University, 2019)
Much research has been conducted and published regarding choice behavior and the concept that less is more. Too many choices can cause cognitive overload for users, lead to choice paralysis, and negative emotions. Past research has also studied and published regarding choices and the older adult population in specific. The research has established that older users prefer fewer options than their younger counterparts. Choice overload’s application to UX is not as well known. Therefore, a further area to study is whether there is a difference between the older and younger generations regarding the preferred amount of options given on an interface. This study conducted two rounds of testing. The purpose of the first round of testing was to confirm that the elderly favor fewer options on an interface. The purpose of the second round of testing was to help determine guidelines for designers concerning specific choice set sizes. The results of the testing supported prior research regarding the senior population’s preferences; however, guidelines for choice set size were not able to be determined. The findings of the study added support to other user-experience elements such as filtering, navigation systems, and aesthetics.
Keywords: UX Design; User Experience Design; choice overload; choice paralysis; choice theory; choice set size; senior population; older adults